Analysis of the Role of Pokdarwis in the Development of Tourism Villages in Matangaji Kapubaten Cirebon - Yuke Hernawati; Fitriatunnisa Shabrina (Jurnal Toursci, 2026)
Background. The development of community-based tourism villages is a tourism development strategy that aims to improve the welfare of local communities while maintaining the sustainability of natural and cultural resources. One of the key actors in the development of tourism villages is the Tourism Awareness Group (Pokdarwis), which serves as a driver, manager, and facilitator of tourism activities at the village level. Aims. This study aims to analyze the role of Pokdarwis in the development of Matangaji Tourism Village, Cirebon Regency; identify factors that support and hinder their role; and formulate strategies to enhance their contribution to the sustainable development of tourism villages. Method. This study employs a qualitative descriptive approach, collecting data through in-depth interviews and field observations. The research informants include Pokdarwis administrators, village officials, and communities involved in village tourism activities. The data were analyzed through the stages of data reduction, data presentation, and drawing conclusions to obtain a comprehensive picture of the role and dynamics of Pokdarwis in the development of tourist villages. Results. The study results indicate that the Matangaji Village Pokdarwis play a relatively strategic role in the development of tourist villages, particularly in driving community participation, managing tourism activities, and promoting local tourism potential. However, this role is suboptimal due to limited human resource capacity, limited funding, and insufficient stakeholder synergy. The main supporting factors include local tourism potential, community support, and institutional legitimacy from the village government, while the inhibiting factors include the lack of training, mentoring, and cross-sector coordination. Conclusion. Based on these findings, this study recommends a strategy to expand the role of Pokdarwis by strengthening human resource capacity, strengthening institutional and organizational governance, increasing funding, and enhancing stakeholder collaboration. This strategy is expected to promote the sustainable development of Matangaji Tourism Village in Cirebon Regency by empowering local communities.